The influence of the stagnation zone on the fluid dynamics at the nozzle exit of a confined and submerged impinging jet - Jeffers, N; Stafford, J; Conway, C; Punch, J; Walsh, E (Springer Berlin Heidelberg, 2016)
Low profile impinging jets provide a means to achieve high heat transfer coefficients while occupying a small quantity of space. Consequently, they are found in many engineering applications such as electronics cooling, annealing of metals, food processing, and others. This paper investigates the influence of the stagnation zone fluid dynamics on the nozzle exit flow condition of a low profile, submerged, and confined impinging water jet. The jet was geometrically constrained to a round, 16-mm diameter, square-edged nozzle at a jet exit to target surface spacing (H/D) that varied between 0.25<h .="" 0<h="" 1350<re<17,300="" a="" accurate="" across="" after="" also="" an="" and="" are="" at="" before="" between="" both="" boundary="" choice="" chosen="" commissioned="" conditions="" confined="" confinement="" constraints.="" custom="" d="" d,="" d<1="" d<8.75="" data="" designed="" dynamics="" exit="" exit,="" exits="" facility="" flow="" fluid="" focus="" for="" found="" guide="" h="" heights="" however,="" image="" impinging="" in="" influence="" influences="" inlet="" is="" it="" its="" jet="" l="" laminar="" length="" low="" main="" mean="" measure="" measurement="" model="" models,="" necessary="" normalised="" nozzle="" nozzle.="" numerical="" objective="" of="" order="" paper="" paper;="" particle="" particular="" present="" presented="" presented.="" primary="" profile="" profiles="" quantitatively="" regard="" regimes="" relevance="" results="" revealed="" similar="" simulations="" stagnation="" statistics="" strongly="" suggest="" that="" the="" this="" to="" tube="" turbulence="" turbulent="" utilise="" velocimetry="" velocity="" view="" was="" with="" zone="">0.5 —where D is the inner diameter of the jet—in order to minimise modelling uncertainty.</h>